Emerging roles of Aurora-A kinase in cancer therapy resistance - Dayong Zheng; Jun Li; Han Yan; Gang Zhang; Wei Li; Edward Chu; Ning Wei (Elsevier, 2023)
Aurora kinase A (Aurora-A), a serine/threonine kinase, plays a pivotal role in various cellular processes, including mitotic entry, centrosome maturation and spindle formation. Overexpression or gene-amplification/mutation of Aurora-A kinase occurs in different types of cancer, including lung cancer, colorectal cancer, and breast cancer. Alteration of Aurora-A impacts multiple cancer hallmarks, especially, immortalization, energy metabolism, immune escape and cell death resistance which are involved in cancer progression and resistance. This review highlights the most recent advances in the oncogenic roles and related multiple cancer hallmarks of Aurora-A kinase-driving cancer therapy resistance, including chemoresistance (taxanes, cisplatin, cyclophosphamide), targeted therapy resistance (osimertinib, imatinib, sorafenib, etc.), endocrine therapy resistance (tamoxifen, fulvestrant) and radioresistance. Specifically, the mechanisms of Aurora-A kinase promote acquired resistance through modulating DNA damage repair, feedback activation bypass pathways, resistance to apoptosis, necroptosis and autophagy, metastasis, and stemness. Noticeably, our review also summarizes the promising synthetic lethality strategy for Aurora-A inhibitors in RB1, ARID1A and MYC gene mutation tumors, and potential synergistic strategy for mTOR, PAK1, MDM2, MEK inhibitors or PD-L1 antibodies combined with targeting Aurora-A kinase. In addition, we discuss the design and development of the novel class of Aurora-A inhibitors in precision medicine for cancer treatment.